Model Pendampingan Nasabah oleh Bank Wakaf Mikro dalam Membangun Kemandirian Usaha - Jakaria Rumakway; Fadlan Rumakway; Nani Hanifah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Bank Wakaf Mikro (BWM) is a sharia-based microfinance institution established by the Financial Services Authority (OJK) in Indonesia, operating within Islamic boarding school (pesantren) environments. This study analyzes the client assistance model applied by Bank Wakaf Mikro in fostering entrepreneurial independence among micro-enterprise communities. Using a qualitative approach with secondary data sourced from official OJK reports, academic journals, policy documents, and case studies. from multiple BWM units, the study identifies that BWM implements a structured and integrated assistance model encompassing pre-financing education, business mentoring, group-based financing, and spiritual coaching (halaqah). The findings reveal that this multi-layered mentorship model contributes significantly to improved financial literacy, business capacity, and social capital among.beneficiaries. The study concludes that the pendampingan model at BWM represents an effective socio-economic empowerment mechanism, and recommends its scaling through stronger stakeholder collaboration and digital integration.